Pengaruh E-Service Quality dan Customer Experince Terhadap Keputusan Penggunaan Layanan Wifi - Ridwan Alief Ramdhan Adi; Rr. Rochmoeljati (Yayasan Literasi Sains Indonesia, 2023)
This research aims to explore the relationship between e-service quality and customer satisfaction with WiFi services, as well as identifying the correlation between customer satisfaction and repurchase intentions. In addition, this research also shows customer experience as a factor that influences customer satisfaction, and tests whether e-service quality can mediate the relationship between customer satisfaction and repurchase intention. A survey method using a questionnaire was used to collect data from 15 respondents, who were WiFi service customers aged at least 17 years, domiciled in DKI Jakarta. The results of hypothesis testing show positive results and a significant impact on all formulated hypotheses, providing an important contribution to our understanding of the factors that influence customer satisfaction in the context of WiFi services. It is hoped that these findings can serve as a guide for service providers to improve e-service quality and increase customer satisfaction. Apart from that, this research also explores the influence of customer satisfaction on repurchase intentions. By focusing on the context of WiFi services, the findings of this research can provide valuable insights for practitioners in designing more satisfying marketing and service development strategies. The analysis results show that customer satisfaction not only has a positive impact on repurchase intention, but also has an important role in linking customer experience with satisfaction levels.